Factors affecting the use of electronic cigarettes in Udayana University students - Luh Pitriyanti; Dewa Nyoman Wirawan; Komang Ayu Kartika Sari; I Made Ady Wirawan; Desak Putu Yuli Kurniati (Universitas Udayana, 2018)
Background and purpose: Electronic cigarettes (e-cigarettes) have been marketable since 2003 and first became for sale in Indonesia in 2010. Users tend to be predominately young people. The purpose of this study is to determine the proportion, characteristics and factors that influence the use of e-cigarettes among university students. Methods: This study used a cross sectional survey with 351 undergraduate students from a variety of study programs at Udayana University. Students were selected by multistage random sampling. In the first step, 10 out of 47 study programs at Udayana University were chosen randomly. Students who responded by filling out online questionnaires were included in this study. Data collection was conducted using questionnaires with the Survey Monkey Application. Analysis with logistic regression was applied to determine the factors influencing e-cigarettes use. Results: The proportion of university students who used tobacco cigarettes was 14.53%. The number of respondents who reported had ever used e-cigarettes was 61 (17.38%, 95%CI: 13.46%-21.3%) and 25 of them (40.98%) were current smokers. As many as 88.52% of respondents who had ever used e-cigarettes were male and 11.48% were female. Students who had ever used e-cigarettes in the campus area were 22 (36.07%). The reasons of using e-cigarettes included a desire to stop using tobacco cigarettes (29.51%), the fact that e-cigarettes are considered safer (26.23%), are considered “cool” (22.95%) and other reasons (26.23%). Multivariate analysis showed that the variables found to be associated with the use of e-cigarettes were gender (AOR=14.72; 95%CI: 4.34-49.87), a history of smoking tobacco cigarettes (AOR=42.16; 95%CI: 13.56-131.08), a history of consuming alcoholic beverages (AOR=5.72; 95%CI: 2.04-16.04) and coming from a smoking household (AOR=3.87; 95%CI: 1.33-11.21). Conclusion: The proportion of university students who had ever used e-cigarettes was found to be higher than tobacco cigarettes users. In addition, use was found to be greater among male students than females. Influencing factors associated with the use of e-cigarettes are gender, a history of tobacco smoking, a history of consuming alcoholic beverages and coming from a smoking household. There is a need for prevention efforts including education and regulations to reduce the use of e-cigarettes among students as well as community in general.